Produção e caracterização de recobrimentos de aço, empregando a liga amorfizável Fe-Cr-Nb-B - Melle, Ana Karla (2012)
The equipments used to oil flow are submitted in an aggressive environment with the presence of hydrogen sulphide, carbon dioxide and sand, which contribute to corrosion and wear of the surface. To resist of these requests one alternative is the inner coating using materials with high properties of corrosion and wear. Amorphous coatings iron based have good prospects for this application. These alloys, beyond high properties, are low cost system and, therefore, they are viable economically. In this context, the aim of this work is the production and the characterization of coatings, using the amorphous alloy Fe60Cr8Nb8B24 (%at), with special focus on hardness and wear properties. Initially, preliminary studies were made for the evaluation of glass forming ability for selected composition and the influence of impurities on this behavior. The second step of this work was the production of coatings through two different routes. The first was thermal spraying process LVOF (low velocity oxygen fuel), with utilization of two distinct raw materials: (i) amorphous powders produced by atomization and (ii) amorphous powders made by high energy milling. In the other route, coatings were manufactured by spray forming process using prelayer of nickel alloys, whose aim was to allow the adhesion of particles on the substrate. All coatings produced were characterized using X-ray diffraction (XRD), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), wear and hardness tests and porosity and oxygen content measurements. The results shown the feasibility of production of amorphous coatings by the two routes analyzed, with interesting properties when compared to conventional materials.